Madura foot: Report of a eumycetoma Moroccan case - Naoufal Hjira; Adil Boudhas; Abderrahmane Al Bouzidi; Mohammed Boui (Wolters Kluwer Medknow Publications, 2015)
Madura foot is a chronic infectious disease, caused by bacterial actinomycetes or by fungi. Mycetoma is endemic in tropical and subtropical areas, where it is a real public health issue. It is a rare and neglected disease in our country. The diagnosis is made by clinical picture, direct microscopic examination and histological study. The best therapeutic choice is surgical removal of the lesion, followed by medical treatment. An earlier diagnosis and treatment can elicit good results. We report a case of eumycetoma in a 33 year-old Moroccan man, rural worker, treated by Ketoconazole in 12 months, associated with surgical debridement. The evolution was marked by the complete remission of the infection.